Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.1 - Solving Quadratic Equations by Completing the Square - Exercise Set: 43


$y=(\frac{-1+\sqrt 29}{2}, \frac{-1-\sqrt 29}{2})$

Work Step by Step

Step-1 : Add $7$ on both sides of the equation $y^2+y=7$ Step -2 : Add the square of half of the co-efficient of $y$ to both sides. Co-efficient of $y =1$ Half of $1 = \frac{1}{2}×1=\frac{1}{2}$ Square of $\frac{1}{2}$ is $\frac{1}{2}×\frac{1}{2}=\frac{1}{4}$ The equation becomes $y^2+y+\frac{1}{4}=7+\frac{1}{4}$ Step-3 Factor the trinomial and simplify the right hand side. $(y+\frac{1}{2})^2=\frac{28+1}{4}$ $(y+\frac{1}{2})^2=\frac{29}{4}$ Step-4 Use the square root property and solve for $y$ $(y+\frac{1}{2})=±\sqrt\frac{29}{4}$ Step-5 Subtract $\frac{1}{2}$ on both the sides $y=-\frac{1}{2}±\sqrt \frac{29}{4}$ Step-6 Simplify the right hand side $y=-\frac{1}{2}±\frac{\sqrt 29}{2}$ $y=-\frac{1±\sqrt 29}{2}$ Therefore the solution set is $(\frac{-1+\sqrt 29}{2}, \frac{-1-\sqrt 29}{2})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.